APPLICATION OF FRUIT BAGGING, SANITATION, AND YELLOW STICKY TRAP TO CONTROL THRIPS ON MANGOSTEEN - ., Affandi; Emilda, D.; A.S, M. Jawal (Indonesian Journal of Agricultural Science, 2008)
Scars on mangosteen fruits caused by thrips are the mostprominent constraint in Indonesian export of mangosteen.Most of the exported mangosteen are rejected due to scarappearance. This research aimed to study the effects of fruitbagging, sanitation, and sticky trap application on the scarintensity on mangosteen. The research was conducted at afarmers polycultured mangosteen orchard in Lima Puluh Kota,West Sumatra, Indonesia from September 2006 to February2007. The mangosteen trees were cultured with cacao andcoconut. To study the effects of bagging on the number of scars,the fruits were individually bagged at different time pointsstarting from the time of calyx falling down (0) followed at 2,4, 6, 8, 10, 12, and 14 weeks later. Each treatment was replicatedsix times. The experiment of sanitation (SNT) and yellowfluorescent sticky trap (YST) application was designed in acompletely randomized design with six replications, except forthe control which was replicated only three times. Four treatmentsstudied were SNT, YST, combination of SNT+YST, andcontrol. The sanitation was applied by removing all weeds underthe canopy of mangosteen trees followed with soil tillage andfogging. The sticky trap was nailed on woody sticks and placedon 3 m above the ground at four different positions around thetree canopy. Parameters observed were the percentage and intensityof scars and number of thrips caught on the sticky traps.The results showed that application of early bagging, SNT, YST,and SNT+YST were effective to reduce intensity and percentageof scars. However, combination of SNT+YST demonstrated thebest results in reducing the intensity and percentage of scars by32.14% and 42.82%, respectively. Combination of SNT+YSTalso drastically decreased thrips population as indicated by thelow number of thrips catched after five biweekly observations.Since the fifth observation, the thrips population was low (lessthan 5 thrips catched per sticky trap) and far below the economicthreshold. The present study implies the importance of earlyfruit bagging, sanitation, and sticky trap application in protectingmangosteen fruits from scars.